The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.09.16.508252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with misdiagnosis of hospitalised patients in general hospitals of Central Uganda

Abstract: Misdiagnosis of inpatients is a major public health issue whose scope and causes are unknown in Sub-Saharan African countries. The purpose of this cross-sectional study, which was conducted in five hospitals in central Uganda, was to identify the factors associated with inpatient misdiagnosis in general hospitals in Central Uganda. Records of 2,431 patients admitted between July 1st, 2019 and June 30th, 2020 were specifically reviewed to obtain data on variables thought to be associated with misdiagnosis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…Failure to obtain and use accurate patients' weights is associated with increased errors in medication dosing and subsequently suboptimal treatment, antimicrobial resistance, and drug toxicities (12)(13)(14). According to a study conducted in four hospitals in Uganda, 58% of the health workers witnessed medication errors and from a review of documents, medication errors were among the most frequent kind of errors, accounting for 17.2% of all the errors (15). In another study, drug overdose was found to be the most common medication error, accounting for 42.9% of all medication errors (16).…”
Section: Introductionmentioning
confidence: 99%
“…Failure to obtain and use accurate patients' weights is associated with increased errors in medication dosing and subsequently suboptimal treatment, antimicrobial resistance, and drug toxicities (12)(13)(14). According to a study conducted in four hospitals in Uganda, 58% of the health workers witnessed medication errors and from a review of documents, medication errors were among the most frequent kind of errors, accounting for 17.2% of all the errors (15). In another study, drug overdose was found to be the most common medication error, accounting for 42.9% of all medication errors (16).…”
Section: Introductionmentioning
confidence: 99%